Wearable technologies as extensions: a postphenomenological framework and its design implications. Issue 2 (4th March 2023) - Rapp, Amon
ABSTRACT: Wearable technologies are increasing both in number and variety enabling new ways for collecting personal data, as well as novel interaction modalities. Even though the Human-Computer Interaction (HCI) community has widely explored the potential applications of wearables, its theoretical contribution on this research field has been far from impressive. Most scholars and designers seem to rely on a series of dominant assumptions that look at wearables "from the outside" by focusing on their "external properties." When these assumptions are fully embraced at design-time, however, they may cloud opportunities for designing for the "internal aspects" of our everyday experience. In this article, I propose a theory that looks at wearables "from the inside, "giving a theoretical backdrop to all those wearable designs that pay attention to the internal aspects of interaction. By adopting a postphenomenological approach, I conceptualize wearable devices as "extensions" of our intentionality and introduce the "extension relation" to explain how wearables may alter how we relate to the world. In doing so, I propose a series of design considerations that aim to trace future research lines for all those wearables that are currently designed from an "externalistic" perspective.